Reduced thermal sensitivity and increased opioidergic tone in the TASTPM mouse model of Alzheimer's disease. Issue 10 (October 2016) - Aman, Yahyah; Pitcher, Thomas; Simeoli, Raffaele; Ballard, Clive; Malcangio, Marzia
Abstract : Abstract: Individuals with Alzheimer's disease (AD) are in susceptible patient groups in which pain is an important clinical issue that is often underdiagnosed. However, it is unclear whether decreased pain complaints in patients with AD result from elevated pain tolerance or an impaired ability to communicate sensations. Here, we explored if AD-related pathology is present in key regions of the pain pathway and assessed whether nociceptive thresholds to acute noxious stimulation are altered in the double-mutant APPswe × PS1.M146V (TASTPM) transgenic mouse model of AD. TASTPM mice exhibited an age-dependant cognitive deficit at the age of 6 months, but not at 4 months, a deficit that was accompanied by amyloid plaques in the cortex, hippocampus, and thalamus. In the spinal cord, β-amyloid (APP/Aβ) immunoreactivity was observed in dorsal and ventral horn neurons, and the expression of vesicular glutamate transporter 2 (VGLUT2) was significantly reduced, while the expression of the inhibitory peptides enkephalins was increased in TASTPM dorsal horn, consistent with an increased inhibitory tone. TASTPM mice displayed reduced sensitivity to acute noxious heat, which was reversed by naloxone, an opioid antagonist. This study suggests that increased inhibition and decreased excitation in the spinal cord may be responsible for the reduced thermal sensitivity associated with AD-related pathology. Abstract : Increased inhibition and decreased excitation in the spinal cord may be responsible for the reduced thermal sensitivity in TASTPM transgenic mouse model of Alzheimer disease.